Unconventional superconductors anisotropy and multiband effects - Askerzade, Iman (Springer Series in Materials Science, 2012)
This book deals with the new class of materials unconventional superconductors, cuprate compounds, borocarbides, magnesium-diboride and oxypnictides. It gives a systematical review of physical properties of novel  superconductors. There is an increasing number of fundamental properties of these compounds which are relevant to future applications, opening new possibilities. The theoretical explanation is presented as generalization of Ginzburg-Landau phenomenology and microscopical Eliashberg theory for multiband and anisotropic superconductors. Various applications of this approachs and time dependent version of two-band Ginzburg-Landau theory are considered. An important topic are fluctuations in two-band and anisotropic superconductors. Significant  new results on current problems are presented to stimulate further research. Numerous illustrations, diagrams and tables make this book useful as a reference for students and researchers.